2007
DOI: 10.1243/09544119jeim235
|View full text |Cite
|
Sign up to set email alerts
|

Short-fibre reinforcement of calcium phosphate bone cement

Abstract: Calcium phosphate cement (CPC) sets to form hydroxyapatite, a major component of mineral bone, and is gaining increasing interest in bone repair applications. However, concerns regarding its brittleness and tendency to fragment have limited its widespread use. In the present study, short-fibre reinforcement of an apatitic calcium phosphate has been investigated to improve the fracture behaviour. The fibres used were polypropylene (PP) fibres, 50 microm in diameter and reduced in length by cryogenic grinding. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 13 publications
3
20
0
Order By: Relevance
“…Also the toughness of the cement increased as composites did not fracture after reaching the yield strength but were kept together by the elongated microspheres. Similar mechanical characteristics are also observed using fiber-containing calcium phosphate cements [23,24]. Compared to these fiber-containing cements, microsphere/calcium phosphate cement composites are more easy to process with respect to injectability and polymer distribution and therefore can form an attractive alternative.…”
Section: Discussionsupporting
confidence: 60%
“…Also the toughness of the cement increased as composites did not fracture after reaching the yield strength but were kept together by the elongated microspheres. Similar mechanical characteristics are also observed using fiber-containing calcium phosphate cements [23,24]. Compared to these fiber-containing cements, microsphere/calcium phosphate cement composites are more easy to process with respect to injectability and polymer distribution and therefore can form an attractive alternative.…”
Section: Discussionsupporting
confidence: 60%
“…Being aware on the excellent bioresorbability of DCPD and CDHA, researchers are focused on attempts to overcome the mechanical weakness of the self-setting calcium orthophosphate formulations by using different fillers, fibers and reinforcing additives that give rise to formation of various multiphasic biocomposites [104,105,109,199,259,274,409,[412][413][414][415][416][417][418]. Even carbon nanotubes have been successfully tested to reinforce the self-setting formulations [419].…”
Section: Reinforced Self-setting Formulations and Concretesmentioning
confidence: 99%
“…Efforts have been directed toward increasing the tensile strength of CPCs through the fabrication of CPC-fiber composites [27,[49][50][51]. The incorporation of fibers such as Vicryl ® (Ethicon, NJ, USA) and carbon nanotubes (CNTs) into CPCs enhanced their flexural strength and the work of fracture is directly dependent on the fiber content, length and strength [27,49].…”
Section: Clinically Available Ibcsmentioning
confidence: 99%
“…The incorporation of fibers such as Vicryl ® (Ethicon, NJ, USA) and carbon nanotubes (CNTs) into CPCs enhanced their flexural strength and the work of fracture is directly dependent on the fiber content, length and strength [27,49]. Buchanan et al demonstrated that the incorporation of polypropylene fibers into CPC resulted in an increase in the work of fracture and setting time, as well as a decrease in the compressive strength and modulus [50]. However, the major drawbacks of the currently available fibers include low fiber-matrix interface bonding and a lack of bioresorbability and bioactivity.…”
Section: Clinically Available Ibcsmentioning
confidence: 99%